Kidz Bop: Re-packaged Music; How “censored” music teaches children gender role conformity, race identification, and KGOY. - Reasor, Halston Ashley (URJ-UCCS: Undergraduate Research Journal at UCCS, 2017)
Children in the U.S are viewed as a demographic of consumers, and to continue selling products to children means that medias need to create kid friendly material that can be sold to children. Kidz Bop is a series of musical covers that sells “age appropriate” music to children by having children sing popular songs on the radio and occasionally perform the songs in music videos. While Kidz Bop is an attempt to cover music created by adults to sell to younger individuals, the “age appropriate” idea of Kidz Bop is perpetuating the sociological phenomenon KGOY and teaching children inappropriate messages about adult situations as well as gender role conformity and race identification (Bell 2015; Kurnit 1999).